Lived-Experiences and Intelligence Scores of Working Students in Bachelor of Science in Medical Laboratory Science Program at University of Minda-nao - Silguera, Junelle P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study assesses lived experiences and measures working students' intelligence scores enrolled in Bachelor of Science in Medical Laboratory Science Program at the University of Mindanao last 1st semester, S.Y. 2022-2023. This study employs a mixed-method approach, specifically a concurrent triangulation strategy of quantitative and qualitative analysis. Further, this study used a survey questionnaire to get quantitative data and conducted in-depth interviews to get qualitative data. Based on the quantitative result, participants have high intelligence scores, and it is oftentimes manifested. On the other hand, qualitative results showed these dominant themes: exploring beyond limits, providing own needs and the needs of the family, working while studying is not for everyone, and taste the bitterness of reality. The qualitative themes suggesting challenges and realities faced by working students may influence their intelligence scores, with those experiencing greater adversity potentially demonstrating lower scores due to increased stress and distraction. The research implication of this study underscores the importance of recognizing the multifaceted challenges faced by working students and their potential impact on academic performance, specifically intelligence scores.